14‐3‐3ζ targeting induced senescence in Hep‐2 laryngeal cancer cell through deneddylation of Cullin1 in the Skp1‐Cullin‐F‐box protein complex. (21st June 2019) - Seo, Sung Bin; Baek, Ji‐Ye; Lim, Ji‐Hee; Jin, Xuyan; Lee, Mun‐Yong; Lee, Jeong‐Hwa
Abstract: Objectives: Despite of the aberrant expression of 14‐3‐3ζ in head and neck squamous cell carcinoma (HNSCC), little is known about the role of 14‐3‐3ζ in the regulation of senescence in HNSCC. This study was performed to investigate whether 14‐3‐3ζ is implicated in senescence evasion of Hep‐2 laryngeal cancer cells. Methods: The expression of 14‐3‐3ζ was suppressed using RNA interference strategy. Senescence induction was determined by senescence‐associated β‐galactosidase staining and the numbers of promyelocytic leukaemia nuclear body. Real‐time PCR, western blotting and immunohistochemistry were applied for the expression of corresponding proteins. Xenograft experiment was performed to show in vivo effect of 14‐3‐3ζ silencing on tumour growth. Results: 14‐3‐3ζ silencing significantly induced senescence phenotypes via 27 accumulations. Subsequently, we demonstrated that p27 accumulation is linked to inactivation of SCF Skp2 complex activity, probably due to the deneddylation of cullin‐1 (Cul‐1) as follows. (a) Neddylated Cul‐1 is decreased by 14‐3‐3ζ silencing. (b) Blocking neddylation using MLN4924 reproduces senescence phenotypes. (c) Knockdown of CSN5, which functions as a deneddylase, was shown to restore the senescence phenotypes induced by 14‐3‐3ζ depletion. Finally, we demonstrated that 14‐3‐3ζ depletion effectively hindered the proliferation of Hep‐2 cells implanted into nude mice. Conclusion: 14‐3‐3ζ negatively regulates senescence in Hep‐2 cells, suggesting that 14‐3‐3ζ targeting may serve to suppress the expansion of laryngeal cancer via induction of senescence through the Cul‐1/SCF Skp2 /p27 axis.